An Analysis of English Pronunciation Made by Students with Makassarese Accent in Pronouncing Plosive Voiceless Consonants - Ahmad Shideng; Maemuna Muhayyang; Muhammad Arham Basri (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2025)
This study investigates the challenges faced by students at IMMIM Boarding School in Makassar regarding the pronunciation of plosive voiceless consonants (/p/, /t/, /k/). Using descriptive qualitative analysis, the research identifies the types and causes of pronunciation errors and explores the teacher's role in addressing these issues. Data were collected from 19 second-grade students through pronunciation tests, recordings, and teacher interviews. The results revealed a total of 98 errors, with omission being the most prevalent. Internal factors such as age and motivation, along with external factors like language exposure, contributed to these errors. The findings emphasize the need for targeted instructional strategies to improve pronunciation skills.